PENGEMBANGAN MODUL GEOMETRI RUANG BERBASIS STRUCTURED INQUIRY UNTUK SISWA KELAS V SD - Atikah Rahma; Iva Sarifah; Nidya Chandra Muji Utami (Prima Magistra: Jurnal Ilmiah Kependidikan, 2021)
This research was aimed to produce mathematic module in the content of space geometry. The method used in this research is research and development (R&D) with an adaptation of ADDIE development models. This research can only carried out from expert judgment, which media expert, material expert, and language expert. The collection data techniques include interview, and questionnaire. The result for this space geometry module obtained 90.00% from materials expert, 80.80% from media expert, and 84.00% from language expert. Based on the results from the three of expert, obtained an average score 83.84%. It shows that space geometry module based on structured inquiry can be categorized as very good with score range 81%-100%, and it can be use as one of teaching suplementary material’s reference for space geometry content to upgrade the concepts understanding of 5th grade elementary school students.